Motif Penggunaan Media Sosial Twitter (Studi Deskriptif Kuantitatif Pada Pengikut Akun Twitter @EXOind) - Dhea Nursyafitri Liani; Nofha Rina (Cakrawala - Jurnal Humaniora, 2020)
The number of active internet users in Indonesia is increasing every year. This proves that Indonesian people more often access media that are connected to the internet, one of which is social media. Easy to use and allows for interaction without any distance and time limit makes people use social media including fandom. Twitter is a social media that is used by fandom as a means to carry out fangirling activities. The purpose of this study is to ascertain the motives of followers from Twitter account @EXOind in using social media Twitter. This study uses a motive category reference from Papacharissi and Rubin (2000). This study uses survey methods with descriptive analysis and quantitative approaches. The questionnaires were distributed to 100 respondents using a Likert scale. The result shows that the Information Seeking Motive and Entertainment Motive are in the very high category. While the Convenience Motive, Interpersonal Utility Motive, and Pass Time Motive are in the high category.Motive, Social Media, Twitter, K-Pop, Fandom